Differentiation of water sources and hydrological thresholds of herb-to-shrub communities across a revegetated chronosequence in Baijitan National Nature Reserve, China: a quantitative analysis using hydrogen-oxygen stable isotopes - Shunxia, Wang; Na, Zhang; Yifei, Hu; Xiaojing, Ma; Hongbin, Ma (Frontiers in Plant Science, 2026)
IntroductionPlant water-use strategies are critical for maintaining community stability during ecological restoration in arid regions. This study aims to quantify the proportional contributions of different water sources to dominant plant species across a restoration chronosequence and to assess their impact on the stability of shrub-grass ecosystems.MethodsThe research was conducted within the Ningxia Baijitan National Nature Reserve, China, using a restoration chronosequence (1953-2020) that included natural vegetation areas. Samples of plant xylem water, soil water (0-120 cm depth), and precipitation were collected. Stable isotope ratios (δ²H and δ¹⁸O) were analyzed, and Bayesian mixing models (MixSIAR) were applied to quantify the proportional contributions of different soil layers to plant water uptake. The grass-to-shrub water use ratio (Rh/s​) was defined to characterize ecosystem stability, and its theoretical threshold was validated using a mathematical model.Results(1) Significant vertical differentiation in water sources existed among functional groups: shrubs predominantly relied on deep soil water (40-100 cm; 52.3% contribution), semi-shrubs primarily used intermediate depths (20-40 cm; 19.8%), while herbaceous species concentrated uptake in shallow layers (0-20 cm; 78.6%). (2) The proportion of deep-soil water used by shrubs increased significantly with vegetation age, whereas semi-shrubs showed a positive but non-significant trend for mid-layer water use, and herbs exhibited no significant differences across the restoration chronosequence. (3) Ecosystem stability thresholds based on Rh/s ​were identified: strong stability when Rh/s​<0.9, semi-stability when 0.9<Rh/s<1.4, and instability when Rh/s​>1.4. This interval division was confirmed by a mathematical stability analysis calculating the real parts of eigenvalues.DiscussionThe results confirm that vegetation restoration facilitates a complementary water-use strategy. The stability-maintaining mechanism can be described as shrubs enhancing drought resilience by accessing deep water reserves, while herbaceous species foster community renewal through rapid exploitation of shallow resources. This underscores the key role of plant water-use strategies in the ecological reconstruction of arid regions.